The efficacy of Instagram on biology undergraduate students in University of Ilorin, Nigeria - Mulkah Adebisi Ahmed (University of Muhammadiyah Malang, 2020)
Instagram is one of social media commonly used and has influential power among people for sharing ideas, instructional media, and social interaction. This study aimed at examining the efficacy of Instagram on Biology students in University of Ilorin. This quasi experimental study included 75 undergraduate students of University of Ilorin, Nigeria majoring in Biology and Biology Education. Instagram Learning Content Course ware, Instagram Biology Test, Instagram Biology Marking Guide, and Daily Lesson Plan were the instruments used in data collection process. Furthermore, the data gained were analyzed using t-test and ANCOVA. The results revealed that there was significant difference existed between biology Major and Biology Education students in their learning achievement [t(74) = 17.852, p<.05]. In contrast, there was no significant difference between male and female students in learning as they utilized Instagram in learning process [F(10,25) = 2.129, p>.05]. In conclusion, the more attention is crucial to be pain for students in their learning process, particularly in the media used.